Padang Halal Tourism: Studi Kasus Terhadap City Branding Pada Pusat Perdagangan Kota Padang - Fitri Adona; Yusnani Yusnani; Sukatik Sukatik (Politeknik Negeri Padang, 2019)
Since West Sumatra established itself as the world's best halal tourist destination at the World Halal Tourism Award 2016, Padang City is automatically synonymous with the city of